Recent advances in the molecular pathology, cell biology and genetics of ciliopathies. Issue 5 (4th January 2008) - Adams, M; Smith, U M; Logan, C V; Johnson, C A
Abstract : Primary cilia have a broad tissue distribution and are present on most cell types in the human body. Until recently, they were considered to be redundant organelles, but progress over the past 5 years has led to an understanding of their role in normal mammalian development. The class of inherited disorders that involve aberrant ciliary function are known as ciliopathies, and although their range of severity can vary, they share some common and unexpected clinical phenotypes. The aim of this review is to assess recent insights into the structure, function and formation of primary cilia, and relate this to the pathology, molecular genetics and cell biology of the ciliopathies.